Research trends in digital marketing and data-driven marketing: A bibliometric analysis - Tuğçe Acar Kara; Ferhat Orman (Управленец)
The accelerated development of digital technologies and the Internet stimulates the transition from the traditional to the digital model of marketing. The study presents a bibliometric analysis to examine international publications in the field of digital marketing (DM) and data-driven marketing (DDM) with a holistic approach, determine the current level of research interest in the topic under review and identify key development trends. The fundamental principles of bibliometrics and scientometric management constitute the methodological framework of the paper. Among the research methods applied are statistical and scientometric analyses. The data used in the study were retrieved from the Web of Science. Bibliometric analysis was carried out with 1,541 and 58 articles on digital and data-driven marketing, respectively. The data set covers the period of 2006–2024, when the first study on digital marketing emerged, and the period of 2003–2024 for data-driven marketing. The obtained data were processed using the R Project. The findings indicate a constantly growing research interest in the concepts under consideration. We have identified journals with most publications on digital marketing (Sustainability) and data-driven marketing (Journal of Business Research); established the countries publishing most studies on DM (USA) and DDM (China); and revealed the most frequently used keywords in DM (‘impact’) and DDM (‘management’). The results of keywords’ occurrence analysis were utilized to create thematic maps for visualizing motor, niche, basic and emerging/declining research areas in the field of digital and data driven marketing.